A hydrovoltaic power generation system based on solar thermal conversion. (August 2022) - Li, Lianhui; Feng, Sijia; Du, Lang; Wang, Yongfeng; Ge, Changlei; Yang, Xianqing; Wu, Yue; Liu, Mengyuan; Wang, Shuqi; Bai, Yuanyuan; Sun, Fuqin; Zhang, Ting
Abstract: Water evaporation-driven hydrovoltaic generators (HGs) with the property of sustainable electricity generation offer the promise of clean and renewable power. Despite recent efforts to advance HGs by enhancing solid-liquid interface interactions and nanopore structures design, extremely scarce usable natural water source and slow heat replenishment remain obstacles. Here, we demonstrated a solar thermal conversion boosted hydrovoltaic power generation system (HPGS) by rationally integrating environmental water harvesting patterned coating, solar steam generator and hydrovoltaic functional coating with solar thermal conversion capability. In the system, the water collected or readily available in the environment with high ion concentration (conductivity of 505.95 μS cm −1 ) is purified by a solar steam generator into a low conductivity pure water (~ 6.32 μS cm −1 ) to supply for HGs, realizing the solution to the water source limitation for HGs. The Al2 O3 /CB nanoparticles constructed hydrovoltaic functional coating exhibits remarkable solar thermal conversion ability to raise device temperatures by over 18 °C, resulting an increase of V oc by 130.7% from 2.54 V to 5.86 V at 50% RH under 1 standard sun radiation. Such HPGS based on solar thermal conversion makes it possible for HGs to directly use the environmental available water and break through the shackles of restricted ambient temperature and slow heat replenishment. Graphical Abstract: TOC : A solar thermal conversion boosted hydrovoltaic power generation system (HPGS) is designed to achieve continuous high performance electricity generation using the environmental easily available unclean water. By electrode design, the balance between water climbing height, water evaporation speed and the output performance is achieved. As the results, V oc increases by 130.7% from 2.54 V to 5.86 V at 294.6 K and 50% RH under 1 standard sun radiation. ga1 Highlights: A solar thermal conversion boosted HPGS is designed for electricity generation using easily available unclean water. HG temperature can be raised by over 18 °C, resulting an increase of V oc from 2.54 V to 5.86 V under 1 sun radiation. The balance between water climbing height, evaporation rate and device output performance under sunlight is achieved. The Al2 O3 /CB coating can be well scraped coated on walls to achieve performance expansion to power for electronics.